Western impressions of the Hong Kong health care system. - Bennett, C L (1996)
Hong Kong, Taiwan, Singapore, and Malaysia are initiating health care reform to meet the changing demands of populations with improved socioeconomic status and access to modern technologies and who are living longer than in previous generations. Hong Kong, in particular, is facing a unique set of circumstances as its people prepare for the transition in 1997 from a British colony to a Special Administrative Region of China. While spending only 4% of its gross domestic product on health care, it has a large and regulated public hospital system for most inpatient medical care and a separate, loosely regulated private health care system for most outpatient medical care. In 1993 the Secretary for Health and Welfare of Hong Kong initiated a year-long process to debate the pros and cons of 5 fundamental programs for health care reform. After a year of open consultation, options were chosen. We describe the Hong Kong health care system, the fundamental changes that have been adopted, and lessons for reformers in the United States.